Benthic ecological restoration under the combined action of slow-release oxygen material and benthic organisms. (August 2022) - Dong, Ziyi; Wang, Ying; Fu, Jun; Liu, Xianjing; Pei, Yuansheng; Chen, Zehao
Abstract: The oxygen level is key benthic ecosystem health. In this study, a new kind of slow-release oxygen material (SROM) was developed and evaluated in a simulation experiment. The effects of SROM dose and dosing method on the pH and DO, the release of nitrogen and phosphorus, and greenhouse gas emissions were studied. The restoration of typical benthic species ( Ceratophyllum represented submerged plants and Cipangopaludina cahayensis represented benthic animals) was also evaluated based on the analysis of catalase and peroxidase activities, survival rate, and biomass. The result shows that dosing SROM on mud surfaces had a better effect than dosing in mud. When dosing SROM on the surface of mud at a suitable dose, the DO of water increased from 0.5 mg/L to higher than 4 mg/L, and the pH was below 9, which would be suitable for the survival of benthos. Dosing SROM could also cause the concentrations of nutrient elements (NH4 + -N, TN, TP, and PO4 3− ) in overlying water and the emission flux of CH4 and CO2 to decrease. In addition, the growth of Ceratophyllum and Cipangopaludina cahayensis was accelerated, which benefited the restoration of benthic ecosystems. For microbial community structure, various of bacteria for nitrogen and the phosphorus cycle were found in the sediment (including aerobic denitrifying bacteria). Dosing SROM could increase the Simpson index of the bacterial community, means an increase in bacterial diversity. The results show that the dosing of SROM could be an effective method in the early stage of benthic habitat restoration. Graphical abstract: Image 1 Highlights: A slow-release oxygen material (SROM) used for lake restoration was developed. SROM could restrain the release of NH4 + -N, TN, TP, and PO4 3− . SROM could restrain the emission of CH4 and CO2 . The growth of benthos was accelerated after dosing SROM. Dosing of SROM could increase the bacterial diversity in sediments.